2016
DOI: 10.1177/1071100716658456
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Sesamoid Position Influence on Functional Outcome and Satisfaction After Hallux Valgus Surgery

Abstract: Level III, retrospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
(31 reference statements)
3
46
1
Order By: Relevance
“…Previous studies have suggested that reduction of the sesamoids is important for prevention of recurrence and postoperative patient-reported outcomes. 4,24 However, sesamoid position did not correlate with first metatarsal pronation in our study, and there is no literature on the effect of pronation on clinical outcomes in HV. Small differences in angles may have significant consequences on patient-reported outcomes in foot and ankle surgery.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies have suggested that reduction of the sesamoids is important for prevention of recurrence and postoperative patient-reported outcomes. 4,24 However, sesamoid position did not correlate with first metatarsal pronation in our study, and there is no literature on the effect of pronation on clinical outcomes in HV. Small differences in angles may have significant consequences on patient-reported outcomes in foot and ankle surgery.…”
Section: Discussioncontrasting
confidence: 75%
“…Postoperatively, two-thirds of the patients in our study had "reduced" sesamoids as defined by Esemenli et al (sesamoid station of grade 1 or less), which is similar to prior studies evaluating sesamoid position following DCO. 3,4,8,17,27,28,33 Though most of the patients in the cohort had adequate sesamoid reduction, nearly half of the patients did not have significant improvement in sesamoid station. Sesamoid position has been shown to be correlated with postoperative functional outcomes and patient satisfaction 4 as well as maintenance of HV correction.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that there is a significant relationship between reduction of TSP and recurrent deformities. 4,20 Okuda et al 20 showed that incomplete sesamoid reduction can lead to recurrent hallux valgus. The current study demonstrated an average TSP improvement of 2.5 positions.…”
Section: Discussionmentioning
confidence: 99%
“…The mean TSP of 2.3 (±1.0) is well within the acceptable postoperative position of 4 or less. 4,20 We understand this measurement is not likely related to the hardware construct, but it is an interesting variable to note. The authors feel the described technique of a small first interspace incision allows for compete release of the lateral sesamoid complex.…”
Section: Discussionmentioning
confidence: 99%